2015
DOI: 10.18488/journal.110/2015.1.2/110.2.36.45
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Veterinary Inspection Practices on Quality of Beef Produced In Ibarapa Central Local Government Area of Oyo State, Nigeria

Abstract: Beef is an important animal protein source in Nigerian diet and its quality depends on intrinsic and extrinsic attributes. Hence, this study was carried out to assess veterinary inspection practices on quality of beef produced in Ibarapa Central Local Government Area of Oyo State, Nigeria. The findings of this study showed that the butchers were young with mean age of 40.51years and 95.70% were males. All the respondents strongly agreed that facilities such as lighting, carcass carriers, security fence and coo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
0
0
Order By: Relevance
“…Meanwhile, there has not been any legislation on abattoir hygiene since the colonial era in Nigeria (Lawan et al, 2013). The urgent need for repairs and replacement of infrastructures in the slaughterhouses in Nigeria was highlighted by Lawan et al (2013) and Oyediran, (2015) who reported that all the major abattoirs in the Northern and Southern regions of the country were in a deplorable situation and could no longer support the production of safe and wholesome meat. This has impacted negatively on the environment and public health at large (Istifanus & Bwala, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, there has not been any legislation on abattoir hygiene since the colonial era in Nigeria (Lawan et al, 2013). The urgent need for repairs and replacement of infrastructures in the slaughterhouses in Nigeria was highlighted by Lawan et al (2013) and Oyediran, (2015) who reported that all the major abattoirs in the Northern and Southern regions of the country were in a deplorable situation and could no longer support the production of safe and wholesome meat. This has impacted negatively on the environment and public health at large (Istifanus & Bwala, 2017).…”
Section: Resultsmentioning
confidence: 99%